An endstation for resonant inelastic X‐ray scattering studies of solid and liquid samples. (1st December 2016) - Yin, Zhong; Peters, Hans-Bernhard; Hahn, Ulrich; Gonschior, Josef; Mierwaldt, Daniel; Rajkovic, Ivan; Viefhaus, Jens; Jooss, Christian; Techert, Simone
Abstract : A novel experimental setup is presented for resonant inelastic X‐ray scattering investigations of solid and liquid samples in the soft X‐ray region for studying the complex electronic configuration of (bio)chemical systems. The uniqueness of the apparatus is its high flexibility combined with optimal energy resolution and energy range ratio. Abstract : A novel experimental setup is presented for resonant inelastic X‐ray scattering investigations of solid and liquid samples in the soft X‐ray region for studying the complex electronic configuration of (bio)chemical systems. The uniqueness of the apparatus is its high flexibility combined with optimal energy resolution and energy range ratio. The apparatus enables investigation of chemical analyses, which reflects the chemical imprints. The endstation is composed of a main sample chamber, a sample holder for either solid or liquid jet delivery system, and a soft X‐ray grating spectrometer for 210–1250 eV with a resolving power of ∼1000. It combines for the first time liquid jet technology with a soft X‐ray spectrometer based on the variable line spacing principle. This setup was commissioned at the soft X‐ray beamline P04 at PETRA III of the Deutsches Elektronen‐Synchrotron in Hamburg which is currently the most brilliant storage‐ring‐based X‐ray radiation source in the world. The first results of liquid and solid samples show that this setup allows the detection of photons across an energy range of ∼300 eV. This covers simultaneously the emission lines of life‐important elements like carbon, nitrogen and oxygen in a shot‐based procedure.